Indirect Right Inguinal Hernia in a Six-Year-Old Girl: A Case Report and Literature Review - Gusti Putu Agung Pratama P (Fakultas Kedokteran Universitas Pelita Harapan, 2026)
Background: Pediatric inguinal hernia is a common surgical problem, yet direct hernias in girls account for fewer than 1.5% of childhood groin defects. Although often painless and reducible, the cumulative risk of incarceration approaches 6%, warranting early repair. Case Description: A healthy six-year-old girl presented with a two-month history of an intermittent, painless right-groin bulge that appeared with crying or coughing. Physical examination revealed a 2.5 × 2 cm fully reducible mass; ultrasonography confirmed a fat-containing herniation medial to the inferior epigastric vessels, consistent with a reducible direct inguinal hernia. After optimization, she underwent an open high ligation herniotomy. The hernia sac was dissected to the internal ring and securely ligated without mesh. Operative time was 25 minutes and blood loss were negligible. The patient was discharged the same day, resumed unrestricted activity within one week, and remained asymptomatic at six-month follow-up with no evidence of recurrence. Conclusions: This case illustrates that open high ligation provides safe, durable closure for the exceedingly rare direct inguinal hernia in pediatric females, mirroring success rates above 98% reported for indirect defects. Early elective repair eliminates the risk of incarceration, avoids mesh-related morbidity, and allows rapid return to normal activity.